Соотношение полов и продолжительность жизни черноморских веслоногих рачков — Copepoda (Crustacea) в лабораторных условиях - Сажина, Л.И. (Вестник зоологии, 1972)
Experimental observation was carried out of four Copepoda species from the Black Sea. In the process of ontogenesis the ratio of males and females was studied as well as. the life longeivity of both. The quantitative predominance of females in the plankton can be explained by two factors - different life longevity of males and females and starting sex composition of population. The life longeivity in fernales in eurythermal species is 2.5-3. months, in stenothermal - 1.5 -2 months; life longeivity weeks of males is not more than 2